DEVELOPMENT OF A WEB-BASED GROUP VISIT RESERVATION SERVICE AT THE ARCHIVES AND LIBRARY OFFICE OF MAGETAN REGENCY - Aulya Putri Dzulfiga; Adi Prasetyawan; Shamila Mohamed Shuhidan (JIPI (Jurnal Ilmu Perpustakaan dan Informasi), 2026)
This study aims to develop a website-based group visit reservation service for public libraries using the Waterfall development model, consisting of analysis, design, implementation, testing, and maintenance stages, in order to address inefficiencies and scheduling conflicts caused by manual reservation systems. The system was developed using Laravel, PHP, and MySQL, and evaluated through expert validation and field testing involving 15 respondents, resulting in scores of 95% for media validation, 88% for material validation, and 96% for field testing, all categorized as “very feasible.” Beyond its local implementation, this study highlights the practical significance of the system in supporting digital transformation in public libraries by improving service efficiency, enabling real-time scheduling, and enhancing user accessibility. Furthermore, the integration of features such as online booking, automated confirmation, and reminder notifications demonstrates a contribution to the development of more systematic, transparent, and technology-driven library services